Production of Volvariella volvacea mushroom using oil palm empty fruit bunch as substrate in Hutan Simpan Ayer Hitam, Puchong - Hasim, Nur Najma Athirah (2019)
Volvariella volvacea is an edible mushroom and has been cultivated in China. In China, this mushroom also known as warm mushroom as it needs a warm temperature to grow well. The growing stages are divided into two which is button stage and mature stage. The mature stage is when it is in egg stage, elongate stage and when the volva is ruptured. This study was conducted in Hutan Simpan Ayer Hitam, (HSAH), Puchong and the objectives were to determine the effect of some microclimatic factors, and environment factors EFB bed condition and bed orientation on V.volvacea mushroom production and to investigate the suitable microclimate of tropical forest and suitable bed orientation that promotes mushroom production in HSAH. The Empty Fruit Bunch (EFB) was used as compost material and 20 replicates of EFB bed were made with two different orientations, North-South and East-West. The process of mushroom harvesting took 30 days respectively and the total and weight recorded into the excel software. The results of the study showed that, microclimatic factors, bed condition and bed orientation did not give the significance effect towards mushroom production. Based on the analysis, the suitable microclimate and environmental condition was in HSAH that promote 44.5 kg mushrooms are 26˚C to 30˚C, with relative humidity is 70-90 %, pH is 6-7 in between, moisture content is 3 (dry+) to 6 (normal+) with light intensity were 570.7 lux.